2021
DOI: 10.3389/fmicb.2021.587431
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Chili Damping-Off Disease, Caused by Pythium myriotylum

Abstract: Pythium myriotylum is a notorious soil-borne oomycete that causes post-emergence damping-off in chili pepper. Of various disease management strategies, utilization of plant growth promoting rhizobacteria (PGPR) in disease suppression and plant growth promotion is an interesting strategy. The present study was performed to isolate and characterize PGPR indigenous to the chili rhizosphere in Pakistan, and to test the potential to suppress the damping-off and plant growth promotion in chili. Out of a total of 28 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 133 publications
0
8
0
1
Order By: Relevance
“…In addition, Hyder et al (2021) showed that the effects of Bacillus sp. on the germination rate of chili pepper seeds and its potential function as a biocontrol agent were evaluated by measuring the antagonistic effect and germination rate against the Pythium pathogen [ 37 ]. Analysis of the germination rate of corn and pepper seeds treated with TSA32-1 showed a higher germination rate than when each pathogen was treated alone ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Hyder et al (2021) showed that the effects of Bacillus sp. on the germination rate of chili pepper seeds and its potential function as a biocontrol agent were evaluated by measuring the antagonistic effect and germination rate against the Pythium pathogen [ 37 ]. Analysis of the germination rate of corn and pepper seeds treated with TSA32-1 showed a higher germination rate than when each pathogen was treated alone ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corn and pepper seeds treated with TSA32-1 were infected with soil-borne pathogens, and the sprout germination rate showed a tendency to increase when compared to the values of those infected with pathogens alone. Soil-borne pathogens like F. graminaearum and Pythium infection mainly occur in seeds, seedlings, and young roots, and it is known that it has a significant impact on the growth of seedlings, causing great economic loss and a ripple effect [ 37 ]. Against these soil-borne pathogens, TSA32-1 may contribute to the control effect that helps prevent disease in seeds.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to several reasons, including infection with many pathogens, especially those affect the roots, bases of stems and seedlings. Phytophthora spp., Pythium spp., Rhizoctonia spp., Fusarium spp., Macrophomina phaseolina are the most important pathogenic fungi [6][7][8][9][10]. They are the main causes of rotting of the roots of pepper IOP Publishing doi:10.1088/1755-1315/1262/3/032009 2 leading to significant economic losses and reduction in the amount of production in protected and open cultivation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Los hongos que afectan el cultivo de chile son Phytophthora capsici, Fusarium sp., Sclerotiorum sp., Rhizoctonia solani y Pythium causando el Damping off o la marchitez (Morra y Bilotto, 2015;Hyder et al, 2021). Para contrarrestar los problemas de fertilidad en los suelos y presencia de enfermedades, los productores se apoyan con el uso de productos químicos, los cuales, al hacer uso excesivo de estos, provocan contaminación en los ecosistemas y el medio ambiente, resultando la salinidad del suelo, la eutrofización del agua y la acumulación de nitritos y nitratos, mismos que pueden ser una fuente de contaminación ambiental y una amenaza para la salud humana (Castellanos et al, 2017).…”
Section: Introductionunclassified